1982
DOI: 10.1007/bf00268649
|View full text |Cite
|
Sign up to set email alerts
|

Bridging large bone defects with a xenograft composited with autologous bone marrow

Abstract: We have investigated the role of defatted, decalcified xenogenic bone implants composited by impregnation with fresh autologous marrow in bridging large cortical defects. Diaphyseal cortical implants were obtained from orthopaedic operations on humans and from guinea pigs and prepared by treatment with acetone, 0.6 M HCl and ethanol. The composited graft was used to bridge a 3 cm defect in the diaphysis of the ulna of rabbits. Periodic investigations were made clinically, radiographically and histologically an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Xenografts lose their osteogenic and osteoinductive properties during chemical cleaning performed to coun- teract their antigenic properties and prevent transmission of infection [16,17] . Since they cause a hypersensitivity reaction in the host, obstruction develops in the vessels formed between donor tissue and host bed and sequestration in the graft.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Xenografts lose their osteogenic and osteoinductive properties during chemical cleaning performed to coun- teract their antigenic properties and prevent transmission of infection [16,17] . Since they cause a hypersensitivity reaction in the host, obstruction develops in the vessels formed between donor tissue and host bed and sequestration in the graft.…”
Section: Discussionmentioning
confidence: 99%
“…Some experimental and clinical trials performed after this development have shown that impregnation of various types of bone graft with autologous red marrow has had beneficial effects on osteogenesis [10,11,16,[19][20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this effect has been shown to be dose dependent (Harris et al 1968, Kruger 1975, Norton et al 1968, Yen & Shaw 1972. In the dosage schedule used by us it did not seem to inhibit 'neoosteogenesis' (Gupta & Tuli 1980, Gupta et al 1982. Some osteons showed all the three rings with very narrow central canal, showing that this osteon had formed and virtually matured during 1 month, the period of three dosages.…”
Section: Discussionmentioning
confidence: 90%
“…Mare cortical bone xenografts of low antigenicity have been successfully produced by a cycle of boiling and freezing (Fujinaga and Koike, 1976). Gupta et al (1982) compared defatted and decalcified xenogenic bone implants in large cortical defects repair and reported a high success rate. Zhao et al (1998) reported a successful result using bovine bone graft for the reconstruction of anterior base defects in humans.…”
Section: Discussionmentioning
confidence: 99%